Antibiotic Resistance Patterns and Evaluation of Treatment of Inpatient with Urinary Tract Infections in Two Tertiary Care Hospitals at Kathmandu Valley - Adhikari, Pharsuram; Khanal, Dharma Prasad (Journal of Pharmacy Practice and Community Medicine)
Urinary tract infections (UTIs) is a common bacterial infection in humans of all ages but the prevalence increases with increased age. It is one of the most common types of community and hospital acquired infections. It is a common cause of infections among young, sexually active women; an estimated 1 in 3 women will develop a urinary tract infection before the age of 24 years. Escherichia coli are the leading cause of UTI in humans. It is one of the most common pathogen isolated in around 75% of uncomplicated UTI. It is a growing concern worldwide due to increasing rate of antimicrobial resistance. In Nepal, UTIs is also common disease among Nepalese population. According to the annual report of Ministry of health and population 2016/2017 morbidity of UTIs in Nepal was 3,16,711. The descriptive study was conducted in inpatient at MMCH and MMTH, Kathmandu, Nepal from 29th May to 31st August, 2018. The sample size was 200 with the inclusion criteria of provisional diagnosis of UTI and sent urine sample for culture. A descriptive study was designed by taking total 200 samples of UTI admitted in two hospitals MMCH and MMTH. Treatment of UTI before and after antibiotic susceptibility test was analyzed. Antibiotic susceptibility test was done with commonly used antibiotics. During the study period, total 200 patients were admitted with the provisional diagnosis of UTI, among them 57 (28.5%) micro-organism isolated. Urinary tract infection was more common among females than males. E. coli was the most commonly isolated organism. Urinary pathogenesis showed resistance to commonly used antibiotics like Amoxicillin followed by Ceftriaxone, Ofloxacin, Ciprofloxacin and Cotrimoxazole.
Keywords: Urinary tract infection; E.coli; Antibiotic Susceptibility; Antimicrobial Resistance; Empirical therapy